Accidents and injuries due to consumption of alcohol or drugs in patients treated at an emergency room (Revista Latino-Americana de Enfermagem, 2010)
The aims of the study were to describe the differences in alcohol consumption by sex, education and occupation and to understand the effects of the socio-demographic characteristics on alcohol consumption, in 120 emergency room patients. The results showed significant differences for sex (t=-3.570, p